To What Extent Might Identity Theories Help Understand the Learning Process of EFL Learners - Susiati Susiati; Avelia Yonanda Exaputri (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
This study investigates how identity theories help understand thelearning process of EFL learners of Department of EnglishEducation, Faculty of Teacher Training and Education, UniversitasMuhammadiyah Surakarta. Adopting three different views onidentity: psychological, social and negotiated views, this studyexplored the learners‘ identity based on two backgrounds: Islam andJavanese ethnic in English debating activities in a speaking class.Other than the learners’ unwillingness to communicate, the resultsshow there is a similar view of learners from Islamic and Javanesebackgrounds that feminism issues are sensitive case to be debated inthe activities. The gap lies on their personal view that from theperspective of Islam, it is seen as a ‘sinful’ motion. Whereas, fromthat of Javanese ethnic, feminism issues are seen taboo regarding theJavanese value about women as konco wingking (domestic workers).This leads the lecturers to reconsider the motions to be launched inthe debating activities to build a conducive class.